Comprehensive Evaluation of Cultivated Land Quality in Black Soil of Northeast China: Emphasizing Functional Diversity and Risk Management - Huaizhi Tang; Yuanyuan Zhang; Qi Liu; Mengyu Guo; Jiacheng Niu; Qiuyue Xia; Mengyin Liang; Yunjia Liu; Yuanfang Huang; Yamin Du (Applied Sciences)
The cultivated land in the black soil of Northeast China (BSNC), due to long-term high-input and high-output utilization, is facing a series of challenges such as soil erosion, compaction, and nutrient loss. However, the existing cultivated land quality evaluation (CLQE) lacks regional specificity, making it difficult to accurately reflect the cultivated land quality (CLQ) characteristics across different areas. Therefore, this study proposes a comprehensive evaluation framework that integrates both cultivated land functionality and degradation risk, establishing an assessment system consisting of 18 indicators to comprehensively evaluate the CLQ in the BSNC from multiple perspectives. The results indicate that the CLQ in the BSNC exhibits a declining trend from north to south, with second- and third-grade land dominating, accounting for 75.68% of the total cultivated land area. The overall cultivated land functionality increases from west to east, with the Liaohe Plain Region (LHP) performing the best. Low-risk cultivated land is primarily concentrated in the Songnen Plain Region (SNP) and the Western Sandy Region (WS), covering 38.55% of the total cultivated land area. Additionally, this study finds a trade-off between the primary productivity function and the resource utilization efficiency function across different regions, while a synergistic relationship is observed between resource utilization efficiency and soil nutrient maintenance functions. This research emphasizes the necessity of balancing productivity and ecological protection to achieve the sustainable and efficient use of the BSNC.